Emotion recognition and forecasting from wearable data via cluster-guided attention with cross-species pretraining - Wonjik Kim; Gaku Kutsuzawa; Michiyo Maruyama (Intelligent Systems with Applications, 2025)
Wearable devices enable the continuous acquisition of physiological signals, offering the potential for real-time emotion monitoring in daily life. However, emotion recognition remains challenging due to individual differences, label ambiguity, and limited annotated data. This study proposes a lightweight, cluster-guided attention model for binary emotion recognition (positive vs. negative) and forecasting (up to two hours ahead) from wearable signals such as heart rate and step count. To improve generalization, we leverage unsupervised clustering in the latent space and integrate cross-species pretraining using structured behavioral and physiological data from mice. Our framework reduces annotation burden through an emoji-based self-report interface and performs both within- and across-subject validation. Experimental results on human wearable data demonstrate that our method outperforms classical and lightweight deep learning baselines in both accuracy and macro-F1 score, achieving approximately 74.4% accuracy (macro-F1: 71.5%) for current emotion recognition, 72.9% accuracy (macro-F1: 70.7%) for 1-h forecasting, and 65.5% accuracy (macro-F1: 63.0%) for 2-h forecasting. Moreover, mouse-based pretraining yields consistent performance gains, especially at longer-horizon prediction tasks. These findings suggest that biologically informed attention mechanisms and cross-domain knowledge transfer can significantly enhance emotion modeling from low-resource wearable data.